2006
DOI: 10.1038/sj.onc.1209561
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and integrative functional genomics of HCC

Abstract: Global gene expression profiling of hepatocellular carcinoma (HCC) is a promising new technology that has already refined the diagnosis and prognostic predictions of HCC patients. This has been accomplished by identifying genes whose expression pattern is associated with clinicopathological features of HCC tumors. Molecular characterization of HCC from gene expression profiling studies will undoubtedly improve the prediction of treatment responses, selection of treatments for specific molecular subtypes of HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
95
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 69 publications
(79 reference statements)
2
95
0
2
Order By: Relevance
“…For example, genomic and gene expression analyses have identified key dysregulated signal transduction pathways involved in liver carcinogenesis (Thorgeirsson and Grisham, 2002;Ye et al, 2003;Budhu et al, 2006;Lee and Thorgeirsson, 2006). These studies and others have generated a new paradigm of metastasis ( Figure 3) that is not mutually exclusive to the hypothesis of multistage carcinogenesis depicted in Figure 2.…”
Section: Incidence and Etiology Of Hepatocellular Carcinomamentioning
confidence: 99%
“…For example, genomic and gene expression analyses have identified key dysregulated signal transduction pathways involved in liver carcinogenesis (Thorgeirsson and Grisham, 2002;Ye et al, 2003;Budhu et al, 2006;Lee and Thorgeirsson, 2006). These studies and others have generated a new paradigm of metastasis ( Figure 3) that is not mutually exclusive to the hypothesis of multistage carcinogenesis depicted in Figure 2.…”
Section: Incidence and Etiology Of Hepatocellular Carcinomamentioning
confidence: 99%
“…[12] Additionally, a functional polymorphism in the EGF gene is reported to be associated with the risk of development of HCC. [13] Kannangai et al [14] reported overexpression of EGFR associated with late-stage HCC, increased cell proliferation, and degree of tumor differentiation. All these reports support our hypothesis that EGF is a viable candidate for screening for different cirrhotic populations for early detection of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, a variety of genetic and epigenetic alterations were detected in HCCs and to a lesser extent in preneoplastic cirrhotic livers. Later on, DNA microarray analysis led to an extensive integrative approach, leading to the identification of clusters of HCCs associated with patterns of gene expression that allow comparison between HCC phenotypes in experimental and human HCCs (Lee and Thorgeirsson, 2006). In parallel, recent progress has been achieved in understanding the essential role and function that represents dysregulation of pleiotropic growth factors -that is, the insulinlike growth factor-II (IGF-II), hepatocyte growth factor (HGF), transforming growth factor-a (TGF-a), transforming growth factor-b (TGF-b), and wingless (Wnt) -in contributing to proliferation and antiapoptotic behaviour of HCC cells (Breuhahn et al, 2006).…”
mentioning
confidence: 99%